2018
DOI: 10.1177/0363546518808499
|View full text |Cite
|
Sign up to set email alerts
|

Higher Rates of Lower Extremity Injury on Synthetic Turf Compared With Natural Turf Among National Football League Athletes: Epidemiologic Confirmation of a Biomechanical Hypothesis

Abstract: Background: Biomechanical studies have shown that synthetic turf surfaces do not release cleats as readily as natural turf, and it has been hypothesized that concomitant increased loading on the foot contributes to the incidence of lower body injuries. This study evaluates this hypothesis from an epidemiologic perspective, examining whether the lower extremity injury rate in National Football League (NFL) games is greater on contemporary synthetic turfs as compared with natural surfaces. Hypothesis: Incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 38 publications
2
76
0
Order By: Relevance
“…Overall, choosing a shoe with lower rotational traction that results in no consequent detriment to performance (high translational traction) is recommended, assuming the injury risk from other sports extends to soccer [710, 29]. Table 2, S1 Fig, and Fig 3 can be used to help inform footwear selection for players in warm climate zones.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, choosing a shoe with lower rotational traction that results in no consequent detriment to performance (high translational traction) is recommended, assuming the injury risk from other sports extends to soccer [710, 29]. Table 2, S1 Fig, and Fig 3 can be used to help inform footwear selection for players in warm climate zones.…”
Section: Discussionmentioning
confidence: 99%
“…13 American football also involves reactive cutting and is played on natural and synthetic turfs, with Mack et al recently reporting that synthetic turf resulted in 16% more lower extremity injuries than on natural turf. 14 That association became more pronounced as the authors focused on injuries located more distally, 14 supporting epidemiological observations in soccer. [7][8][9][10][11][12] Mack et al concluded that artificial turf has a causal impact on lower extremity injury, attributed to a biomechanical mechanism associated with the shoe-surface interaction and based on biomechanical testing of football cleats on a variety of playing surfaces.…”
mentioning
confidence: 71%
“…Examples include an examination of the association between stadium surfaces-artificial turf versus natural grass-and injury occurrence, a critical question for NFL athletes and clubs. 9,12 Analyses found higher rates of lower extremity injuries on artificial surfaces. Examination of the unaffiliated neurotrauma consultant and athletic trainer spotter programs for concussion detection and epidemiologic descriptions of high-impact injuries are also in progress.…”
Section: Discussionmentioning
confidence: 96%